FILOSOFI NABI IBRAHIM MENCARI TUHAN MELALUI BULAN, BINTANG DAN MATAHARI - Edi Sumanto (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
If the nature of the horizon above  is observed, which  also shows the sun, moon, stars and  so on, so does the earth with all its contents in the  form of humans, animals, plants and  solid objects, there is a close relationship with the complicated balance that smoothes the arrangement between the various colors of nature and that strengthen each other’s circumstances. Everything is a sign and proof of the form of Allah Almighty. In addition to showing the existence of the Substance of Allah SWT also proves the oneness and to His Almighty created it. It seems not to be imagined at all in anyone’s mind that these objects occur  without anyone creating as well as it is impossible to imagine that something created no one made it.